Dyadic Relationship Komunikasi Keluarga pada Pernikahan Masyarakat Patriarki - Aida Maslamah; Nani Muhsin (Universitas Merdeka Malang, 2023)
Communication in a relationship is an important part of building communication between partners and family members. Patriarchal society is an inseparable part of our culture. This culture is deeplyingrained in the social order, to the point that it colors the communication of marital relations, including husband and wife communication, parenting, division of domestic tasks, dominance and power. This study conducts a discourse on the theory of power relations communication by Norah Dubran, this study uses a literature review between dyadic relationship theory in terms of domination and equality with the social order of patriarchal society, to find the relevance of this dyadic theory to the conditions of married couples in a patriarchal society. As well as providing idealrelationship advice in marriage communication.